2013
DOI: 10.1002/lary.23928
|View full text |Cite
|
Sign up to set email alerts
|

Primary inner ear schwannomas: A case series and systematic review of the literature

Abstract: PIES are rare tumors and most commonly involve the cochlea. Tumor location is often associated with clinical presentation and correlates with delay between symptom onset and diagnosis. A watch-and-scan approach is the management strategy of choice in the absence of intractable vertigo or extensive tumor growth. The majority of patients report stable or improved symptoms over time, regardless of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
4
25

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 68 publications
5
87
4
25
Order By: Relevance
“…Surgical ablative treatment would result in total hearing loss in 100% of cases, with some likelihood of facial nerve palsy in 4% of cases, cerebrospinal fluid leakage in 5.4% of cases, and meningitis in 1.8% of cases [4] . In a recent review regarding ILS, among 53% of patients (109 of 189) observed using serial MRI scans, only 3% required surgical removal [3] , supporting the adoption of the wait and scan approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical ablative treatment would result in total hearing loss in 100% of cases, with some likelihood of facial nerve palsy in 4% of cases, cerebrospinal fluid leakage in 5.4% of cases, and meningitis in 1.8% of cases [4] . In a recent review regarding ILS, among 53% of patients (109 of 189) observed using serial MRI scans, only 3% required surgical removal [3] , supporting the adoption of the wait and scan approach.…”
Section: Discussionmentioning
confidence: 99%
“…Kennedy divided ILS into 7 types according to its localization: intracochlear, intravestibular, intracochleo-vestibular, transmacular, transmodiolar, tympano-labyrinthine, and transotic. In 2013, Van Abel et al [3] Surgical removal is reserved to a limited number of cases and mostly depends on age, general condition of the patient, tumor size, location and growth (into the internal auditory canal or middle ear), and the presence of intractable symptoms (vertigo). Surgical ablative treatment would result in total hearing loss in 100% of cases, with some likelihood of facial nerve palsy in 4% of cases, cerebrospinal fluid leakage in 5.4% of cases, and meningitis in 1.8% of cases [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral expansion into the middle ear through breach of the otic capsule and round window is a rare finding [2]. These tumors may also originate from the inner ear [3], and the Kennedy classification system addresses this type [4].…”
Section: Answermentioning
confidence: 98%
“…У 8% хворих виникає рецидив пухлини через 1 рік після її тотального видалення [7]. Причиною продовженого росту можуть бути неадекватна візу-алізація залишків пухлини на лицевому нерві та ПЗН, недостатня візуалізація ВСХ вздовж його осі [8,9]. При поширенні ПЗН у ВСХ виникає необхідність його трепанації, що здійснюють під час мікрохірургічного видалення пухлини [10].…”
Section: Introductionunclassified